ACMEOLOGICAL PROFESSIONAL COMPETENCE OF FUTURE EDUCATORS - Yusupova Habiba Iriskulovna (International Scientific and Current Research Conferences, 2023)
As the landscape of education continues to evolve, the cultivation of professional competence among future educators has emerged as a critical focal point. This article explores the concept of acmeological professional competence within the context of preparing future educators for the complex demands of the teaching profession. Drawing on acmeological principles, the article examines the multifaceted dimensions of professional competence, encompassing not only pedagogical expertise but also the cultivation of personal, social, and emotional intelligence. Through a comprehensive review of relevant literature and empirical studies, the article delineates a roadmap for developing acmeological professional competence, emphasizing the integration of theoretical knowledge, practical skill acquisition, and ethical understanding. Furthermore, the article delves into the role of mentorship, reflective practice, and continuous professional development in nurturing the holistic growth of future educators. By highlighting the significance of acmeological professional competence, this article contributes to the ongoing dialogue on transformative approaches to educator preparation, with implications for curriculum design, teacher training programs, and the evolution of educational practice.